PEMENUHAN HAK-HAK POLITIK PENYANDANG DISABILITAS OLEH KOMISI PEMILIHAN UMUM (KPU) LABUHANBATU PADA PEMILIHAN KEPALA DAERAH TAHUN 2020 : TINJAUAN TERHADAP UU NO.8 TAHUN 2016 TENTANG PENYANDANG DISABILITAS - Harun Amin Sinaga; Mirza Nasution (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: According to a report on the KPU's role in implementing the Political Rights of Persons with Disabilities in the 2020 Regional Head Elections in Labuhanbatu, the organization did a great job of fulfilling its responsibilities, which included making sure that people with disabilities could fully and successfully participate in politics and the public on an equal basis with everyone else and promoting the rights of people with disabilities as outlined in Law No. 8 of 2016 concerning Persons with Disabilities.Due to barriers to government accessibility, a lack of confidence, and a lack of knowledge about their right to participate in and exercise their political voting rights in regional head elections, particularly in Labuhanbatu Regency, the number of people with disabilities who participated in the 2020 regional head elections in Labuhanbatu remained low.  Limited budget funding, poor infrastructure, and inaccurate data on people with disabilities were the KPU's main challenges in handling participation in the regional head elections in Labuhanbatu.  Keyword:KPU, PoliticalRights, PersonswithDisabilities  Abstrak: Bahasa Indonesia: Menurutlaporantentangperan KPU dalammelaksanakan Hak PolitikPenyandangDisabilitasdalamPemilihanKepala Daerah Tahun 2020 di Labuhanbatu, organisasitersebuttelahmelakukanpekerjaan yang hebatdalammemenuhitanggungjawabnya, yang meliputimemastikanbahwapenyandangdisabilitasdapatberpartisipasisecarapenuh dan berhasildalampolitik dan publiksecarasetaradengan orang lain dan mempromosikanhak-hakpenyandangdisabilitassebagaimana yang digariskandalamUndang-Undang No. 8 Tahun 2016 tentangPenyandangDisabilitas. Karena hambatanaksesibilitaspemerintah, kurangnyakepercayaan, dan kurangnyapengetahuantentanghakmerekauntukberpartisipasi dan menggunakanhaksuarapolitikmerekadalampemilihankepaladaerah, khususnya di KabupatenLabuhanbatu, jumlahpenyandangdisabilitas yang berpartisipasidalampemilihankepaladaerahtahun 2020 di Labuhanbatumasihrendah. Keterbatasan dana anggaran, infrastruktur yang buruk, dan data yang tidakakurattentangpenyandangdisabilitasmenjaditantanganutama KPU dalammenanganipartisipasidalampemilihankepaladaerah di Labuhanbatu.  Kata kunci: KPU, Hak Politik, Penyandang Disabilitas